(untitled) (Journal of educational development exploration, 2026)
Starting from the current situation of "skill-based" and "training-based" in the practice of children’s physical education courses, this paper analyzes the practical dilemma that deviates from the concept of "play as the basic activity" advocated by the "Learning and Development Guide for Children aged 3-6". To respond to the inherent needs of children’s learning development integrity and gameplay, the purpose of this study is to explore how to systematically integrate the concept of gamification into curriculum design and form a new STEAM+ physical activity practice model by organically integrating the interdisciplinary and inquiry-based core elements of STEAM education. The study uses action research methods and case analysis methods to carry out iterative development and empirical testing in front-line teaching places. The practical results show that based on the concept of gamification, the reconstructed curriculum model can effectively stimulate children’s interest in active participation, and realize the collaborative and integrated development of cognitive construction, social communication, emotion and physical movement ability in specific physical sports situations, thus providing an operable practical path for deepening the reform and innovation of early childhood physical education curriculum in our country.